50 nifty super origami crafts - Urton, Andrea; Ghaffari, Michelle; Stunton, James; Yamamoto, Neal (Los Angeles : Lowell House Juvenile ; Chicago : Contemporary Books, 1997)
Offers step-by-step instructions for folding paper to create origami crafts. Includes a code indicating the level of difficulty for each.
Keywords: Origami -- Juvenile literature; Origami; Paper work; Handicraft